Examining the effects of alcohol prohibition Laws in Pakistan on public health - Khan, Muhammad Akhtar Abbas; Akhtar, Farzeen (Journal of the Pakistan Medical Association, 2024)
Globally, more than 3.3 million people die of alcohol use every year. Alcohol consumption has a causal association with more than 230 disorders. Pakistan framed its first alcohol prohibition laws in 1977. These laws were further strengthened in 1979 through an ordinance. There is a complete ban on Muslims for alcohol use in the country, while non-Muslims can get a limited quota. There is a punishment of 80 whips for drinking for Muslim citizens. The biggest loophole in the policy is the issuance of quota permits to non-Muslims. These quotas are largely misused by the Muslims in the country. The use of tainted alcohol takes the lives of hundreds of people every year. There is a need to revisit the alcohol policy of Pakistan. There should either be a complete ban on alcohol use for all citizens or the government should take concrete measures for restraining the availability of substandard, or tainted alcoholic beverages. Key Words: Alcohol, Prohibition, Public health, Hudood ordinance, Alcohol-related harm.